Quinazolino-thiadiazoles as antimicrobial agents - Harun Patel; Atul Shirkhedkar; Sanjay Bari; Kamalkishor Patil; Amit Arambhi; Chandrakantsing Pardeshi; Abhijeet Kulkarni; Sanjay Surana (Faculty of Pharmacy, Cairo University, 2018)
In the present research, we report the synthesis and in vitro antimicrobial activity of a new series of novel quinazolino-thiadiazoles as fused pharmacophore (3-20). In general, the results of the in vitro antibacterial activity are encouraging, as out of 18 compounds tested, Compounds 3 and 8 with a 4-chlorophenyl and 4-nitro phenyl at C-2 of thiadiazole and chloromethyl substituent at C-2 of quinazolinone displayed a broad spectrum antimicrobial activity against all the strains, while compounds 13 and 16 again with a 4-chlorophenyl and 4-nitrophenyl at C-2 of thiadiazole and ethyl substituent at C-2 of quinazolinone showed the same potency but with a narrower spectrum (Bacterial and Fungal strains) with MIC values of 62.5 µg/ml. The structures of the compounds were confirmed by IR, 1H NMR, 13C NMR and Mass analysis. It is worth to mention that the combination of two biologically active moieties quinazoline and thiadiazole profoundly influences the biological activity.